HUBUNGAN INDEKS MASSA TUBUH DENGAN TIMBULNYA ACNE VULGARIS PADA MAHASISWA PRODI D3 KEPERAWATAN STIKES BINA SEHAT PPNI MOJOKERTO - Peni, Tri; Moch.Achwandi, (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Acne Vulgaris is a chronic inflammatory disease of the unit pilosebaseus often expressed by many people, especially teenagers. The disease is not fatal, but it is troubling because it reduces confidence and may increase the incidence of anxiety to depression. Obesity is simply defined as a state of excess body fat accumulation. One of the factors suspected to affect the onset of Acne Vulgaris is the body mass index (BMI). The purpose of this study was to determine the relationship of Body Mass Index with the emergence of Acne Vulgaris. This study design was analytic correlation with cross sectional approach. The variables of this study is the Body Mass Index as the independent variable and Acne Vulgaris as the dependent variable. The population in this study were all patients who come to the poly skin in accordance with the criteria and samples taken by purposive sampling technique. Then the data analyzed in the editing, coding, tabulating and tested with spearman test. The results showed respondents who are obese and raised Acne Vulgaris as much as 17 respondents.Spearman test results showed that p = 0.023 and α = 0.05, p <α so that H0 and H1 accepted then there is a relationship between body mass index with the onset of Acne Vulgarisin D3 nursing student stikes healthy Bina Sehat PPNI Mojokerto. The greater the value of Body Mass Index (BMI) greater risk of Acne vulgaris.Keywords: Body Mass Index (BMI), Obesity, Acne Vulgaris